Appreciation to Organic Agriculture Function: Case Study of Rice Farming - Prihtanti, Tinjung Mary (Universitas Negeri Semarang, 2016)
Agricultural activities are not only producing the visible (tangible) output in the form of food but also the non-visible output (non-marketable goods/non-tangible services). Non-visible output refers to a multifunctionality to supply food to ensure the food sufficiency of farmer household and job opportunities at rural area. The article aims to compare the capability of organic rice farming to conventional, to ensure the food sufficiency of farmer household, the economic value of rice farming to produce food, and the economic estimation of rice farming to its function as an job opportunities. The data for the research is collected in Gentungan Village, Mojogedang District, Karanganyar Regency during the crop year of 2015. In order to study the differences of two rice farming systems, the total of 60 farmers, 30 farmers are dealing with organic farming and other 30 farmers from conventional farming, are subjected for the interview in this research. The results found that the food security of organic farming is higher than conventional farming. The organic rice farming gives the economic value as the food producing and the labor-absorbing function in the study area is higher than the Â conventional farming.